Obliterative portal venopathy without portal hypertension: an underestimated condition. (6th September 2015) - Guido, Maria; Sarcognato, Samantha; Sonzogni, Aurelio; Lucà, Maria Grazia; Senzolo, Marco; Fagiuoli, Stefano; Ferrarese, Alberto; Pizzi, Marco; Giacomelli, Luciano; Colloredo, Guido
Abstract: Background & Aims: Obliterative portal venopathy without portal hypertension has been described by a single study in a limited number of patients, thus very little is known about this clinical condition. This study aimed to investigate the prevalence of obliterative portal venopathy and its clinical‐pathological correlations in patients with cryptogenic chronic liver test abnormalities without clinical signs of portal hypertension. Methods: We analysed 482 liver biopsies from adults with non‐cirrhotic cryptogenic chronic liver disorders and without any clinical signs of portal hypertension, consecutively enrolled in a 5‐year period. Twenty cases of idiopathic non‐cirrhotic portal hypertension diagnosed in the same period, were included for comparison. Histological findings were matched with clinical and laboratory features. Results: Obliterative portal venopathy was identified in 94 (19.5%) of 482 subjects and in all 20 cases of idiopathic non‐cirrhotic portal hypertension: both groups shared the entire spectrum of histological changes described in the latter condition. The prevalence of incomplete fibrous septa and nodular regenerative hyperplasia was higher in the biopsies of idiopathic non‐cirrhotic portal hypertension ( P  = 0.006 and P  = 0.002), a possible hint of a more advanced stage of the disease. The two groups also shared several clinical laboratory features, including a similar liver function test profile, concomitant prothrombotic conditions and extrahepatic autoimmune disorders. Conclusion: Obliterative portal venopathy occurs in a substantial proportion of patients with unexplained chronic abnormal liver function tests without portal hypertension. The clinical‐pathological profile of these subjects suggests that they may be in an early (non‐symptomatic) stage of idiopathic non‐cirrhotic portal hypertension. Abstract : See Editorial on Page325